Prevalence of Apical Periodontitis in Endodontically Treated Premolars and Molars with Untreated Canal: A Cone-beam Computed Tomography Study - Karabucak, Bekir; Bunes, Alf; Chehoud, Christel; Kohli, Meetu R; Setzer, Frank (Journal of endodontics, 2016)
The purpose of this retrospective cohort study was to evaluate the incidence of missed canals in endodontically treated teeth in the Greater Philadelphia area patient population and to evaluate the effect of untreated canals on endodontic outcome. A total of 1397 cone-beam computed tomography (CBCT) volumes taken from January 2013 to July 2015 were investigated. Limited view CBCT images were taken with Kodak 9000 3D System field of view at voxel size, 76 μm or Morita Veraviewpocs 3D F40 field of view at voxel size, 125 μm. All root canal-treated premolars and molars were included in the study. Unfilled canals appearing from cementoenamel junction to apex including splitting from a main canal at coronal, mid, or apical third were defined as missed-untreated canal. A periapical lesion was diagnosed when disruption of the lamina dura was detected and the low density area associated with the radiographic apex was at least twice the width of the periodontal ligament space. The overall incidence of missed canals was 23.04%. The incidence of missed canals per tooth was highest in tooth #14 at 46.5% and tooth #3 at 41.3%. The incidence of missed canals was highest in the upper molars at 40.1% and lowest in the upper premolars at 9.5%. There was a significant difference in lesion prevalence when a canal was missed-untreated (P < .05). Teeth with a missed canal were 4.38 times more likely to be associated with a lesion. Limited field-of-view CBCT should be examined before any endodontic retreatment to identify missed canals. This knowledge would not only help clinicians to locate missed canals clinically but would also help in deciding the surgical approach.